2011
DOI: 10.1016/j.foodchem.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxidative treatment on the physicochemical, rheological and functional properties of oat β-glucan

Abstract: a b s t r a c tThe objective of this work was promote oxidation of b-glucan from oat bran with hydrogen peroxide at different concentration levels (0.3%, 0.6% and 0.9% H 2 O 2 ) and reaction times (30 and 60 min), and evaluate the physicochemical and functional properties of isedoxidised b-glucan with in-vitro tests. An increase in carbonyl and carboxyl groups and alterations in swelling power were verified in the oxidised b-glucan. The cholic acid binding capacity increased in the oxidised b-glucan; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
4
41
1
1
Order By: Relevance
“…However, water-binding capacity of the soluble barley b-glucan significantly decreased with increasing oxidative intensity. These results indicate that additional glycosidic linkages were broken, causing a decrease in water retention capacity (Moura et al, 2011). Moura et al (2011) reported that the swelling power of b-glucan decreased as the H 2 O 2 concentration and heating temperature in treatments increased.…”
Section: In Vitro Binding Capacitiesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, water-binding capacity of the soluble barley b-glucan significantly decreased with increasing oxidative intensity. These results indicate that additional glycosidic linkages were broken, causing a decrease in water retention capacity (Moura et al, 2011). Moura et al (2011) reported that the swelling power of b-glucan decreased as the H 2 O 2 concentration and heating temperature in treatments increased.…”
Section: In Vitro Binding Capacitiesmentioning
confidence: 97%
“…These results indicate that additional glycosidic linkages were broken, causing a decrease in water retention capacity (Moura et al, 2011). Moura et al (2011) reported that the swelling power of b-glucan decreased as the H 2 O 2 concentration and heating temperature in treatments increased. Bae et al (2009) verified the reduction of the swelling power in oat b-glucan when the molecule was partially hydrolyzed with cellulose, resulting in a different MW.…”
Section: In Vitro Binding Capacitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Inulin and oat fiber are carbohydrate-derived fat replacers possessing gelling capacity with water and have low calories [6] [7]. Besides theirs health benefits, inulin and oat fiber are also considered to have prebiotic properties such as the ability to situmulate probiotic bacteria without affecting flavour [3] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, these disadvantages can be eliminated by chemical modification of the starch (Pérez-Gallardo et al, 2012). Oxidation is a chemical modification that changes the characteristics and functional properties of polymers (De Moura et al, 2011). Researchers have found that oxidized starch has appropriate properties for creating films (Kuakpetoon & Wang, 2001), with mechanical properties superior to those obtained from native starch (Palma-Rodríguez *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%